The Effects of a Single Oral Dose of Pyridoxine on Alpha-Aminoadipic Semialdehyde, Piperideine-6-Carboxylate, Pipecolic Acid, and Alpha-Aminoadipic Acid Levels in Pyridoxine-Dependent Epilepsy - Wang, Junjuan; Xue, Jiao; Gong, Pan; Wu, Minhang; Yang, Wenshuang; Jiang, Shiju; Wu, Ye; Jiang, Yuwu; Zhang, Yuehua; Yuzyuk, Tatiana; Li, Hong; Yang, Zhixian (Frontiers in Pediatrics, 2019)
Purpose: To evaluate the effects of a single oral dose of pyridoxine on lysine metabolites including α-aminoadipic semialdehyde (a-AASA), piperideine-6-carboxylate (P6C), the sum of AASA and P6C (AASA-P6C), pipecolic acid (PA) and α-aminoadipic acid (α-AAA) in PDE patients. Methods: The lysine metabolites of 15 patients with molecularly confirmed PDE were detected before and 4 hours after taking a single oral dose of pyridoxine respectively, using liquid chromatography-mass spectrometry (LC-MS/MS) method. Five types of samples were freshly prepared, including plasma, serum, dried blood spots (DBS), urine and dried urine spots (DUS). Results: All the patients had been treated with long-term oral pyridoxine for several months to years (4-62 months), with doses of 30-360 mg/d. The concentrations of a-AASA, P6C, AASA-P6C, PA and a-AAA before and after taking a single oral dose of pyridoxine for the same analyte detected in the same type of sample varied among patients. The mean concentrations increased in almost all the metabolites after taking an oral dose of pyridoxine, with or without statistical significance. Whereas, the metabolites concentrations might increase or decrease among different patients, or in different samples of the same patient, without a regular tendency. There was no statistical correlation between the concentrations before and after taking pyridoxine in the same type of sample for most metabolites. Conclusions: No obvious relationship between the metabolite levels or concentration differences and the age, pyridoxine dose (a single oral dose and long-term maintenance dose), duration of treatment or neurodevelopmental phenotype was found at present study. The large individual differences among patients, probably affected by various genotypes, leading to quite different effects of pyridoxine on the change degree of metabolites concentrations. Our study suggested that long-term pyridoxine treatment could control seizures rather than getting lysine metabolites back to normal. In the future, more therapies should be focused to alleviate the metabolites accumulation and further improve the prognosis of PDE.